Madeira vigas de seção composta T tendo o parafuso como elemento de solidarização: vigas de seção composta T tendo o parafuso como elemento de solidarização - Maria Estania Mendonca Passos (1992)
For the purpose of this work a bibliographic study of brasilian and international publications from 1942 until 1991 was performed related to composite wooden structures. Lately, an experimental research about composite T section beams connected by wood screw was developed. Twa kinds of wood were studied: the "Castanheira" (native) and "Pinus Elliotti" (reflorestation). For both web and flange was stablished the Longitudinal Elasticity Modulus (E) by flexural experiment. Values of E for all the member are presented from which E for the composite beam is analitically determined. Composite T section beams were experimented for sereral numbers of wood screw so as to obtain the real inertial moment for the beam, for each quantily of screw. Results are compared to the theorical inertial moment for each number of screw.